Biological feasibility, economic viability and energy efficiency of intercropping fodder sorghum (Sorghum bicolor) in seed crop of dhaincha (Sesbania aculeata) - DHAKA, A K; PANNU, R K; KUMAR, SATISH; MALIK, KARMAL; SINGH, BHAGAT (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted at CCSHAU, Hisar during kharif seasons of 2011 and 2012 with ten treatments in randomized block design replicated thrice to evaluate the intercropping of sorghum (Sorghum bicolor) in dhaincha (Sesbania aculeata) grown for seed. Results revealed that 1:3 row ratio of sesbania and sorghum at 22.5 cm spacing was found most economical and feasible intercropping system among all the treatments with highest sesbania equivalent yield (1.99 tonnes/ha), land equivalent ratio (1.52), system productivity index (1.69 tonnes/ha), monetary advantage index (13 119 Rupees/ha), net return (7.20×103 Rupees/ha), B:C ratio (1.24), Energy productivity (0.21 sesbania equivalent yield (kg/MJ) and system net energy return (625.4×103 MJ/ha) along with 14.8% and 41.3% reduction in sesbania seed yield and sorghum fodder yield, respectively, over sole cropping of both crops. Hence, for seed production sesbania was sown at 90 cm spacing intercropped with three rows of fodder sorghum in between two rows of sesbania to supplement the income of farmers.